Factors associated with overweight and obesity among postgraduate African students in UPM, 2017 - Tukur, Nura (2017)
Introduction: Globally, overweight and obesity are the major public health problem. World Health Organization (WHO) estimated about 1.9 billion adults were overweight out of which more than 600 million were obese in 2014. In a foreign country, student’s lifestyle and behaviour including eating pattern changes very quickly leading to unhealthy habits, which may have negative effect on their health. The changes in the body mass index (BMI) of a foreign student is influenced by various complex factors involving exposure to more stress, sedentary lifestyle, accessibility and availability to familiar food, limited finances, irregular class schedules and overload, and spending more time on studying with less physical activities leading to increased or decreased intake of food or dependence of fast food with less nutritional value.